Bortezomib-Induced Muscle Toxicity in Multiple Myeloma. Issue 7 (19th June 2017) - Guglielmi, Valeria; Nowis, Dominika; Tinelli, Martina; Malatesta, Manuela; Paoli, Laura; Marini, Matteo; Manganotti, Paolo; Sadowski, Radoslaw; Wilczynski, Grzegorz M.; Meneghini, Vittorio; Tomelleri, Giuliano; Vattemi, Gaetano
Abstract: Multiple myeloma (MM) accounts for ∼13% of all hematologic malignancies. Bortezomib treatment is effective in MM, but can be complicated with neurological side effects. We describe a patient with symptomatic MM who had a reversible metabolic myopathy associated with bortezomib administration and pathologically characterized by excessive storage of lipid droplets together with mitochondrial abnormalities. In a single-center prospective study, 14 out of 24 patients with symptomatic MM were treated with bortezomib and, among these, 7 developed muscular signs and/or symptoms. The myopathy was characterized by a proximal muscle weakness involving lower limbs and was an early complication. Complete resolution of muscle weakness occurred after treatment discontinuation. Conversely, none of the patients who received a treatment without bortezomib developed muscular symptoms. Experimental studies demonstrate that in primary human myoblasts bortezomib at low concentrations leads to excessive storage of lipid droplets together with structural mitochondrial abnormalities, recapitulating the pathologic findings observed in patient's muscle. Our data suggest that patients treated with bortezomib should be monitored for muscular signs and/or symptoms and muscle weakness should alert the clinician to the possibility of myopathy. Bortezomib-induced metabolic myopathy is a potentially reversible entity with important implications for management and treatment of patients with MM.